Better Students Ask More Questions.
Solve the following inequality and write your answer using interval notation. x/4x+1...
1 Answer | add yours
Best answer as selected by question asker.
You need to solve the inequality `x/(4x+1) lt 5x/6` , hence you need to move all terms containing x to the left side such that:
`x/(4x+1)- 5x/6 lt 0`
You need to bring the fractions to a common denominator such that:
`(6x - 5x(4x+1))/(6(4x+1)) lt 0`
Opening the brackets yields:
`(6x - 20x^2 - 5x)/(6(4x+1)) lt 0`
`(x-20x^2)/(6(4x+1)) lt 0`
You need to remember that the value of fraction is less than zero if numerator is less than denominator, hence:
`x-20x^2 lt 6(4x+1)`
You need to bring all terms to the left side:
`x - 20x^2 - 24x - 6 lt 0 =gt - 20x^2 - 23x - 6 lt 0`
Multiplying by -1 the sense of inequality reverses such that:
`20x^2+ 23x+ 6 gt 0`
You need to find the zeroes of the quadratic `20x^2+ 23x+ 6= 0,` hence you need to use quadratic formula such that:
`x_(1,2) = (-23+-sqrt(529 - 480))/(40)`
`x_1 = (-23+7)/40 =gt x_1 = -16/40 =gt x_1 = -4/10 =gt x_1 = -2/5`
`x_2 = -30/40 =gt x_2 = -3/4`
Hence, the values of `x in (-oo,-3/4)U(-2/5,oo)` verify the inequality.
Posted by sciencesolve on February 10, 2012 at 11:54 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.